On the Two Working Palettes of Almada Negreiros at DN Building in Lisbon (1939–1940): First Analytical Approach and Insight on the Use of Cd Based Pigments - Gil, Milene (2022)
This paper reports the first analytical approach carried out on two working palettes by Portuguese modernist master Almada Negreiros, found in 1991 behind old wood cabinets at the DN building in Lisbon. This is the only known occasion Almada left behind the color experiments done before starting to paint in the nearby walls and as such, it is a unique opportunity to analyze the materials and painting techniques that were originally used. The analytical setup comprised in loco technical photography in Vis, UVF and NIR; p-OM, spectrophotometry in Vis and h-EDXRF, complemented by OM-Vis, µ-FT-IR and VP-SEM-EDS of painting micro-samples and pigments in powder form. Preliminary results suggested the use of fresco painting technique and revealed some technical details, such as the use of a coarse lime sand finishing mortar mixed with natural vegetable fibers, and the extensive use of cadmium-based pigments that were not commonly used (or even recommended) in an alkaline environment. The Cd pigments were used alone or in mixtures with Fe based pigments in the warm hues and with cobalt and ultramarine blue pigments in some green paint layers. No clear evidence of organic materials that could have been used as binders was detected